A phase III study comparing single-agent olaparib or the combination of cediranib and olaparib to standard platinum-based chemotherapy in recurrent platinum-sensitive ovarian cancer - Liu, Joyce F.; Brady, Mark F.; Matulonis, Ursula A.; Miller, Austin; Kohn, Elise C.; Swisher, Elizabeth M.; Tew, William P.; Cloven, Noelle Gillette; Muller, Carolyn; Bender, David; Moore, Richard G.; Michelin, David Paul; et al. (Journal of clinical oncology, 2020)
Abstract only 6003 Background: Combination cediranib (C) and olaparib (O) improved progression-free survival (PFS) in patients (pts) with relapsed platinum (plat)-sensitive high-grade ovarian cancer (ovca) compared to O alone in a Phase 2 trial (NCT01116648). We conducted this randomized, open-label Phase 3 trial (NCT02446600) to assess whether combination C+O, or O alone, was superior to standard of care (SOC) plat-based therapy in relapsed plat-sensitive ovca. Methods: Eligible pts had recurrent plat-sensitive [ > 6-month plat-free interval (PFI)] high-grade serous or endometrioid, or BRCA-related, ovca. One prior non-plat therapy and unlimited prior plat-therapies were allowed; prior anti-angiogenics in the recurrent setting or prior PARP inhibitor were exclusions. Pts were randomized 1:1:1 to SOC (carboplatin/paclitaxel; carboplatin/gemcitabine; or carboplatin/liposomal doxorubicin), O (300mg twice daily), or C+O (C 30mg daily + O 200mg twice daily). Randomization was stratified by g BRCA status, PFI (6-12 vs > 12 months), and prior anti-angiogenic therapy. Target sample size was 549 pts; primary analysis occurred 2 years after the last pt enrolled. The primary endpoint was PFS. Type 1 error = 0.025 was controlled by a gatekeeping hierarchy that assessed C+O vs SOC, then O alone vs SOC, and finally C+O vs O. All maintenance therapy was prohibited. Results: Between 4FEB2016 and 13NOV2017, 565 pts enrolled (187 SOC, 189 O, 189 C+O), and 528 pts initiated treatment (166 SOC, 183 O, 179 C+O). 23.7% of patients had g BRCAmut. Median follow-up was 29.1 months. 53 pts on SOC initiated non-protocol therapy (predominantly PARP inhibitor maintenance) before disease progression. The hazard ratio (HR) for PFS was 0.856 (95% CI 0.66-1.11, p = 0.08, 1-tail) between C+O and SOC and 1.20 (95% CI 0.93-1.54) between O and SOC, with median PFS of 10.3, 8.2, and 10.4 months for SOC, O, and C+O, respectively. Response rates were 71.3% (SOC), 52.4% (O), and 69.4% (C+O). In gBRCA pts, HR for PFS was 0.55 (95% CI 0.73-1.30) for C+O vs SOC, and 0.63 (95% CI 0.37-1.07) for O vs SOC. In non-g BRCA pts, HR for these comparisons was 0.97 (95% CI 0.73-1.30) and 1.41 (1.07-1.86). No OS differences between arms were observed at 44% events. Pts receiving C+O (vs SOC) had more frequent Grade 3 or higher gastrointestinal (30.1% vs 8.4%), hypertension (31.7% vs 1.8%), and fatigue events (17.5% vs 1.8%). Conclusion: C+O demonstrated similar activity to SOC in relapsed plat-sensitive ovca but did not meet the primary endpoint of improved PFS. Clinical trial information: NCT02446600.